2004
DOI: 10.1557/proc-808-a8.8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Bulk Recombination in Hydrogenated Amorphous Silicon Solar Cells

Abstract: Dark forward bias current, JD-V, characteristics offer a probe for characterizing carrier recombination and the defect states in the intrinsic layers of hydrogenated amorphous silicon (a-Si:H) solar cells. Detailed studies were carried out on such characteristics for the cells with optimized p/i interfaces and high quality i-layers in which the current transport is bulk recombination dominated. It was found that the diode quality factor n is not a constant with bias voltages as has been generally considered. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Although three Gaussians are used to fit the data, they in reality represent two groups of defect states with "Gaussian-like" distributions where the first is located around midgap and the second with a significantly larger density (~ 100 times) around 0.3 eV from midgap. Even more convincing evidence for the validity of the analysis is the fitting of n(V) characteristics, since it is subject to more stringent requirements due to higher sensitivity of n(V) to an exact defect state distribution while J D -V characteristics rely on the integration of the states across the energy gap [4]. To further verify this numerical simulations were carried out using 1-D simulation program AMPS [8].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although three Gaussians are used to fit the data, they in reality represent two groups of defect states with "Gaussian-like" distributions where the first is located around midgap and the second with a significantly larger density (~ 100 times) around 0.3 eV from midgap. Even more convincing evidence for the validity of the analysis is the fitting of n(V) characteristics, since it is subject to more stringent requirements due to higher sensitivity of n(V) to an exact defect state distribution while J D -V characteristics rely on the integration of the states across the energy gap [4]. To further verify this numerical simulations were carried out using 1-D simulation program AMPS [8].…”
Section: Resultsmentioning
confidence: 99%
“…However, there is a lack of correlation between the results obtained on thin films, on which the majority of material characterization was carried out, with the performance and stability of corresponding solar cells [1,2]. From the bias dependence of the differential diode quality factors, n(V), derived from J D -V characteristics, predictions have been made about the defect state distributions in different a-Si:H i-layers [4]. Dark forward-bias current-voltage (J D -V) characteristics have been shown to be a useful new probe for characterizing carrier recombination, identifying the mechanisms limiting a-Si:H solar cell performance, as well as characterizing the defect states in the i-layers of a-Si:H solar cells [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The measurements were carried out on initial states obtained after 4 hrs. of annealing at 170°C with the kinetics characterized without contributions of thermal annealing that in high quality materials is significant even at room temperature [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Since these kinetics also exhibit an (intensity) 2 t dependence they point to a rate equation for the creation of metastable defects, N ms , dN ms / dt ~ (intensity) 2 / N ms , which is suggestive of new creation mechanisms for SWE defects.Recently it has been shown that in solar cells, in which the recombination at the p/i interface is sufficiently reduced, the dark current forward bias (J D -V) characteristics can be directly related to the gap states in the intrinsic layer [5] and this has been utilized in characterizing the gap states and their energy distribution in diluted and undiluted a-Si:H solar cells [6,7]. The evolutions in the defects, created with volume-absorbed red light at open circuit voltage and constant far forward bias currents, were characterized with the Shockley-Reed-Hall recombination obtained from the dark currents under low forward bias voltages.…”
mentioning
confidence: 99%
“…Recently it has been shown that in solar cells, in which the recombination at the p/i interface is sufficiently reduced, the dark current forward bias (J D -V) characteristics can be directly related to the gap states in the intrinsic layer [5] and this has been utilized in characterizing the gap states and their energy distribution in diluted and undiluted a-Si:H solar cells [6,7]. Here we report on the evolution of metastable defect states around midgap in diluted, proto-crystalline, a-Si:H layers of p-i-n cells which is characterized with low forward bias Mater.…”
mentioning
confidence: 99%